Comparative analysis of short-chain fatty acid levels in non-alcoholic steatohepatitis rat model: Impact of high-fat high-fructose (HFHF), high fat, and Western diets - Mustika, Syifa; Handayani, Dian; Rudijanto, Achmad; Santosaningsih, Dewi; Mariyatun, Mariyatun; Gatya, Mifta; Pramesi, Putrika C.; Rahayu, Endang S.; Fajar, Jonny K. (Narra Sains Indonesia, 2024)
The evidence on the role of diets in the production of short-chain fatty acids (SCFAs) was limited. The aim of this study was to assess the potential effects of high-fat high-fructose (HFHF), high-fat, and Western diets on the levels of SCFA. A research experiment employing a post-test-only control group design was carried out from January to April 2022. A total of 27 rats were randomly allocated to each study group. SCFA was measured two weeks after diet administration. Analysis of variance (ANOVA) test was used to analyze the differences among groups, and the effect estimate of each group was analyzed using post hoc Tukey. The concentrations of SCFAs post HFHF diets were recorded as follows: acetic acid at 54.60±10.58 mmol/g, propionic acid at 28.03±8.81 mmol/g, and butyric acid at 4.23±1.68 mmol/g. Following the high-fat diet, acetic acid measured 61.85±14.25 mmol/gr, propionic acid measured 25.19±5.55 mmol/gr, and butyric acid measured 6.10±2.93 mmol/gr. After the administration of Western diet, the levels of SCFA were 68.18±25.73, 29.69±12.76, and 7.48±5.51 mmol/g for acetic acid, propionic acid, and butyric acid, respectively. The level of butyric acid was significantly lower in HFHF diet group compared to the normal diet (mean difference (MD) 6.34; 95%CI: 0.61, 12.04; p=0.026). The levels of acetic acid (p=0.419) and propionic acid (p=0.316) were not statistically different among diet types (HFHF, high-fat, and Western diet). In conclusion, HFHF diet is associated with a lower level of butyric acid than the normal diet in a rat model.